Development of a thiol‐ene based screening platform for enzyme immobilization demonstrated using horseradish peroxidase. (14th August 2017) - Hoffmann, Christian; Pinelo, Manuel; Woodley, John M.; Daugaard, Anders E.
Abstract : Efficient immobilization of enzymes on support surfaces requires an exact match between the surface chemistry and the specific enzyme. A successful match would normally be identified through time consuming screening of conventional resins in multiple experiments testing individual immobilization strategies. In this study we present a versatile strategy that largely expands the number of possible surface functionalities for enzyme immobilization in a single, generic platform. The combination of many individual surface chemistries and thus immobilization methods in one modular system permits faster and more efficient screening, which we believe will result in a higher chance of discovery of optimal surface/enzyme interactions. The proposed system consists of a thiol‐functional microplate prepared through fast photochemical curing of an off‐stoichiometric thiol‐ene (OSTE) mixture. Surface functionalization by thiol‐ene chemistry (TEC) resulted in the formation of a functional monolayer in each well, whereas, polymer surface grafts were introduced through surface chain transfer free radical polymerization (SCT‐FRP). Enzyme immobilization on the modified surfaces was evaluated by using a rhodamine labeled horseradish peroxidase (Rho‐HRP) as a model enzyme, and the amount of immobilized enzyme was qualitatively assessed by fluorescence intensity (FI) measurements. Subsequently, Rho‐HRP activity was measured directly on the surface. The broad range of utilized surface chemistries permits direct correlation of enzymatic activity to the surface functionality and improves the determination of promising enzyme‐surface candidates. The results underline the high potential of this system as a screening platform for synergistic immobilization of enzymes onto thiol‐ene polymer surfaces. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1267–1277, 2017